(untitled) (Annals of Medical Research, 2021)
Aim: This study was carried out to evaluate the oral mucous membranes of patients with chronic obstructive pulmonary disease and to determine the measures taken for the protection of oral mucous membranes. Materials and Methods: This study was carried out as a descriptive and cross-sectional study. This study was carried out with 200 patients admitted to the chest diseases polyclinic and clinic of a hospital. The patient information form, the “Oral Mucosa Risk Assessment Form" and the " Oral Evaluation Guide" were used in the evaluation of data. Results: A significant positive relationship was found between the mean score of oral mucosa risk assessment form and the mean score of oral evaluation guide. A statistically significant positive relationship was found between the mean score of oral mucosa risk assessment form and the mean score of oral evaluation guide and age, year of disease and the duration of inhaler use. Conclusion: According to the results, it was observed that the oral care of COPD patients was moderate; however, they did not pay sufficient attention to tooth brushing. Nursing approaches for the prevention of oral mucous membranes should be determined in patients with chronic obstructive pulmonary disease.